On the Two Lists of ‘Four [Types Of] Words’ (Nāṟ-col) in the Śāstric Descriptions of Tamil - Chevillard, Jean-Luc (Lingua Posnaniensis, 2013)
This article examines, from the perspective of the History of Linguistics, the specifications and the genesis of two distinct lists of four sets of words which are often found in the ancient shastric corpus of the Tamil-speaking South. One of those lists, which is found inside the “pure grammar” component of that technical literature, enumerates ‘nouns’ (peyarc col), ‘verbs’ (viṉaic col), ‘particles’ (iṭaic col), and uric col (lit. ‘appropriate words’), whereas the other list, which reflects the fact that one of the main aims of “grammar” was to describe literature, enumerates ‘simple words’ (iyaṟcol), tiricol (lit. ‘mutant words’ or ‘twisted words’), ‘regional words’ (ticaic col), and ‘Northern words’ (vaṭacol). In both lists, there is an item for which it is difficult to find a simple translation, namely uriccol for the first list and tiricol for the second list. T he difficulty in identifying and explaining the intention of those who coined those terms seems to be in part due to the fact that the texts which the Tamil tradition has transmitted to us are an assemblage of various parts that were once fragments of a “work in progress”, now fossilized, which was partly abandoned, either because another śāstra (that of lexicography) took over part of the descriptive effort, and/or because the ambition to compile a dhātu-pāṭha (the Sanskrit term for a list of verbal roots) for the Tamil language was abandoned, if such a project ever existed. The fact that discontinuities in the transmission of Tamil śāstric literature do exist is attested to, for instance, by the hesitation of traditional commentators, while explaining sūtra TP 385i (alias TP 392p), which is a characterization of marapu (approx. ‘usage’), said to be dependent on the power of ‘the four words’. The commentators are cautious in deciding which of the two lists of ‘four words’ is meant, possibly hoping to suggest that the sūtra might refer to both, because they believe in the “beauty of compromise”.